4 - Reengineering Postgraduate Curricula and its Mode of Delivery: Graduate Students’ Views of Modular Course Delivery at Addis Ababa University - Solomon Areaya,; Ayalew Shibeshi,; Daniel Tefera, (Journal of Higher Education in Africa, 2013)
The purpose of this study was to examine the graduate students’ views regarding the modular course delivery of the master’s programme in Addis Ababa University. It attempted to answer four basic questions: what are the attitudes of the graduate students towards the modular curricula and block teaching mode of delivery? Is there any difference in students’ preference for modular delivery across different colleges/subjects/disciplines? What are the major strengths and weaknesses of modular course delivery as perceived by graduate students? And what are the outstanding academic and administrative problems encountered by the modular course delivery? The study used the survey method supported by qualitative data collection procedures. Questionnaire was employed to collect data from 732 first year graduate students. However, analysis was made on properly completed and returned 724 questionnaires. Besides six focus group discussions were held. The quantitative data were analyzed by using percentages, means and composite scores, standard deviations and analysis of variance and Tukey HSD. The results showed that graduate students’ overall attitude toward the modular programme is positive. The modular delivery was also perceived favorably. However, significant differences were observed between students of different colleges with regard to attitude towards the modular programme, modular delivery and availability and accessibility of module related materials.